Moral judgements and ideological positioning: A critical discourse analysis of Prabowo Subianto’s portrayal in BBC News - Nina Tiya Hara; Rusdi Noor Rosa; Rahmadsyah Rangkuti; Rahmah Fithriani; Alemina Br. Perangin-angin (Englisia: Journal of Language, Education, and Humanities, 2026)
This study examines the discursive representation of Prabowo Subianto, a prominent Indonesian political figure, within a selected corpus of news articles published by the British Broadcasting Corporation (BBC). Employing Critical Discourse Analysis (CDA) as the analytical framework, the research integrated both deductive and inductive analytical approaches. The deductive phase was grounded in Martin and White's (2005) Appraisal framework, which systematically categorized evaluative language into three attitudinal resources: affect, judgement, and appreciation. The inductive phase complemented this by uncovering hidden ideologies embedded within the news texts that may not be explicitly captured by the appraisal system alone. Data annotation was conducted using the UAM Corpus Tool to ensure systematic and replicable identification of attitudinal resources. The quantitative findings reveal that judgement constitutes the most frequently deployed attitudinal resource, accounting for 53.13% of all identified occurrences, followed by affect (30.96%) and appreciation (15.89%). Within the judgement sub-category, negative judgement of propriety, which evaluates behavior according to ethical and moral standards, dominates the discourse at 30.80%, collectively portraying Prabowo as morally problematic. Negative affect, in turn, reflects public fear and anxiety toward Prabowo's personal conduct and political candidacy, while appreciation resources highlight his strategic efforts to secure voter support. The study concludes that the predominance of negative evaluations aligns with the BBC's publicly stated commitment to universal human rights and liberal democratic values. Conversely, the presence of positive evaluations suggests a concurrent journalistic effort to maintain balance and impartiality, reflecting the inherent tension between advocacy-oriented reporting and the normative ideal of journalistic neutrality. These findings contribute to the broader understanding of how international media construct political identities in non-Western contexts and underscore the ideological underpinnings of ostensibly objective news discourse.